PERFORMANCE OF KAMPUNG UNGGUL BALITNAK (KUB) CHICKENS GIVEN PEPAYA TREE EXTRACT (Carica papaya L.) THROUGH DRINKING WATER - F.Y., Urung; Dewi, G. A. M. K.; Astawa, I P. A. (Jurnal Peternakan Tropika; Vol 12 No 4 (2024): Vol. 12 No. 4 Tahun 2024; July - August, 2024)
Balitnak superior native chicken (KUB) is the result of selection of local native chicken female strains. Where it’s performance is largely determined by maintenance management. However, along with the government policy regarding the prohibition of AGP use, it’s necessary to utilise natural ingredients as a substitute for AGP, namely papaya seeds. The purpose of this research was to analyse the performance of KUB chickens fed with papaya seed extract ( Carica papaya L). The research was conducted for 6 weeks at Sesetan Farm on Jl. Raya Sesetan, Gg Markisa, Denpasar. 80 KUB chickens were kept in colony system cages and divided into 4 groups with 4 repetitions of 5 chickens. Each unit was given drinking water adlibitum, with no papaya seed extract added (P0), drinking water with 3%, 4% and 5% papaya seed extract added (P1, P2, and P3). Observations made refer to 5 research variables, namely consumption of feed and drinking water, PBB, final body weight and feed conversion. This research obtained the results that the provision of drinking water with 3%, 4% and 5% papaya seed extract (P1, P2 and P3) didn’t have a significant effect (P>0.05) compared to the control treatment (P0) in terms of feed and drinking water consumed, PBB, final body weight and feed conversion produced. So it can be concluded that the provision of drinking water with papaya seed extract doesn’t affect the performance of Balitnak Superior Village chickens (KUB) aged 2-8 weeks.